Optical Coherence Tomography Angiography - Dita Mintardi; AK Ansyori; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2019)
Optical Coherence Tomography Angiography (OCTA) is a new high-resolution imaging method for visualizing retinal and choroidal circulation without any dye injection By detecting intravascular flow quickly when needed and being able to repeat images, as often as needed, without risk to patients, doctors will value OCTA as one of the most important applications of OCT imaging because of its ability to offer precise visualization of intravascular flow in the inner retina layer and outside, as well as the inner choroid. OCTA uses high-speed structural OCT imaging and provides three-dimensional data about microvascular structures, enabling visualization of the en face apart from the retinal capillary plexus and choriocapillaris, combined with co-registered en face and cross-sectional structural OCT. Although OCTA is a strong modality, it can have imaging artifacts and provide information that is inherently more complex than structural OCT alone. Successful interpretation of OCTA findings requires an understanding of how OCTA works, the relationship of various ocular pathologies to its angiographic features, and integrated assessment of angiographic and structural OCT data.